In our own time (Art of the Western world / executive producer, Perry Miller Adato, 1989)
Examines why the appearance of abstract expression caused the United Statesto become a center for the visual arts. Reviews the diversity of styles in the postwar period, including the work of Pollock, Wharhol, Oldenburg.